Thermofluidic modeling and temperature monitoring of Li-ion battery energy storage system. (25th November 2020) - Tao, Fengbo; Zhang, Weijiang; Guo, Dongliang; Cao, Wenjiong; Sun, Lei; Jiang, Fangming
Highlights: A thermofluidic model for actual Li-ion battery energy storage system is developed. The energy storage system operated under real frequency regulation is simulated. Thermal behaviors of the energy storage system are analyzed. Effectiveness and reliability of temperature monitoring are specially evaluated. Optimized temperature monitoring strategies for practical systems are proposed. Abstract: The battery energy storage system (BESS) is widely used in the power grid and renewable energy generation. With respect to a lithium-ion battery module of a practical BESS with the air-cooling thermal management system, a thermofluidic model is developed to investigate its thermal behavior. The thermal model for a single battery is established and experimentally validated first, and then the thermofluidic model for this battery module is developed based on the single battery thermal model and validated by experimental data also. Simulations are performed considering the practical frequency regulation condition and some hypothetical situations with unexpectedly high heat generation rates. Thermal behaviors of the battery module under different conditions are carefully analyzed. Results show that the fans-on forced air convection cooling reduces the maximum temperature by 0.4 K and makes the maximum temperature appear in a different battery of the BESS module compared with the natural air convection cooling. Especially, the temperature monitoring strategy is studied. Due to technical and cost constraints, only a limited number of temperature monitoring points can be set and the temperature that can be monitored is the battery surface temperature or some connecting bars' surface temperature. The rationality of the locations of different temperature monitoring points is analyzed. The obtained results clearly indicate that enough caution must be paid when setting the temperature monitoring points in practical BESSs. The bad temperature-monitoring strategy may largely underestimate the maximum temperature (by as much as 3 K under the normal frequency regulation condition, and probably much larger under harsh working conditions) in the BESS and fails at reflecting the thermal status of the BESS.